Разработка устройства для определения профиля медицинских пучков ионизирующего излучения - Шарыпова А. Е. Анастасия Евгеньевна; Григорьева А. А. Анна Анатольевна; Милойчикова И. А. Ирина Алексеевна; Булавская А. А. Ангелина Александровна (2022, 2022)
Заглавие с экрана